Żołnierze na nie swojej wojnie. Losy afrykańskich uczestników wWojen światowych we Francji i ich obraz w filmie Camp de Thiaroye .......... 247 - Kościółek, Jakub (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
SOLDIERS IN SOMEONE ELSE’S WAR: THE HISTORY OF AFRICAN SOLDIERS DURING THE WORLD WARS IN FRANCE AND THEIR IMAGE IN THE FILM “CAMP DE THIAROYE” The subject of the article is an analysis of the film Camp de Thiaroye (1988), directed by Ousmane Sembène and Thierno Faty Sow, in its historical and political context. The film’s significance lies in its contribution to the critical discourse on French colonial policy and the treatment of African soldiers who served in the French army. It reconstructs the events at the Thiaroye camp in Senegal, where, on December 1, 1944, French troops brutally suppressed African veterans demanding overdue wages, leading to the deaths of many. The article outlines the historical background of African presence in the French military and the evolution of their image — initially portrayed as “savage beasts,” and later as “children” — and explores how such representations shaped enduring stereotypes and unequal treatment of Black soldiers even after the war had ended. Through a deconstruction of colonial narratives, the filmmakers expose the hypocrisy of the French administration, which relied on African soldiers during wartime but denied them equal rights in its aftermath. The analysis emphasizes the importance of the film as a tool of historical memory — a memory largely absent from French public discourse — and one that reveals the violent nature of colonialism and its long-term consequences for African societies.